Bumetanide As a Candidate Treatment for Behavioral Problems in Tuberous Sclerosis Complex - Vlaskamp, Chantal; Poil, Simon-Shlomo; Jansen, Floor; Linkenkaer-Hansen, Klaus; Durston, Sarah; Oranje, Bob; Bruining, Hilgo (Frontiers in Neurology, 2017)
Background | Recent studies indicate excitatory GABA action in and around tubers in patients with Tuberous Sclerosis Complex (TSC). This may contribute to recurrent seizures and behavioral problems that may be treated by agents that enhance GABAergic transmission by influencing chloride regulation. Case presentation | Here, we used the chloride transporter antagonist bumetanide to treat a female adolescent TSC patient with refractory seizures, sensory hyper-reactivity and a variety of repetitive and compulsive behaviors. Methods | To evaluate the effect of bumetanide on behavior, auditory sensory processing and hyperexcitability, we obtained questionnaire data, event-related potentials (ERP) and resting state EEG at baseline, after three and six months of treatment and after one month washout period. Discussion | Six months of treatment resulted in a marked improvement in all important behavioral domains, as was substantiated by significant changes reported in parent questionnaires. In addition, resting-state electroencephalography and event-related potentials suggested a favorable effect of bumetanide on hyperexcitability and sensory processing. These findings encourage further studies into the potential benefit of bumetanide on the neuropsychiatric outcome of TSC.